SISTEM PENGELOAAN ARSIP SURAT DAN DOKUMEN PADA SEKRETARIAT DAERAH KABUPATEN BENGKALIS - Irawan, Yuda (Riau Journal Of Computer Science, 2020)
Along with the development of current technology, the need for information is increasingly high and continues to grow, so that various kinds of companies and institutions, must have made changes such as computerized systems within the company or its institutions, so that they can compete and improve the quality of work that is very professional. Records or records of activities in an organization are very important to be maintained and managed. Poor management of archives in an institution or office will adversely affect the performance of the office, at this time the Bengkalis district secretariat still records letters still manually, because this secretariat is in need of information systems for processing archives of letters and documents, with the existence of an archive processing system Letters and documents are expected to be helpful for staff performance in each section of the Bengkalis Regency Secretariat. where the processing of letter and document archives can be captured regularly, so that the completed Documents can be directly printed in the recap for the purposes of other agencies that are in need.